Genomic Characterization of Esophageal Squamous Cell Carcinoma Reveals Critical Genes Underlying Tumorigenesis and Poor Prognosis - Qin, Hai-De (Am J Hum Genet, 2016)
The genetic mechanisms underlying the poor prognosis of esophageal squamous cell carcinoma (ESCC) are not well understood. Here, we report somatic mutations found in ESCC from sequencing 10 whole-genome and 57 whole-exome matched tumor-normal sample pairs. Among the identified genes, we characterized mutations in VANGL1 and showed that they accelerated cell growth in vitro. We also found that five other genes, including three coding genes (SHANK2, MYBL2, FADD) and two non-coding genes (miR-4707-5p, PCAT1), were involved in somatic copy-number alterations (SCNAs) or structural variants (SVs). A survival analysis based on the expression profiles of 321 individuals with ESCC indicated that these genes were significantly associated with poorer survival. Subsequently, we performed functional studies, which showed that miR-4707-5p and MYBL2 promoted proliferation and metastasis. Together, our results shed light on somatic mutations and genomic events that contribute to ESCC tumorigenesis and prognosis and might suggest therapeutic targets.